2018
DOI: 10.1142/s0217984918504018
|View full text |Cite
|
Sign up to set email alerts
|

Time-fractional inhomogeneous nonlinear diffusion equation: Symmetries, conservation laws, invariant subspaces, and exact solutions

Abstract: In this paper, a class of time-fractional inhomogeneous nonlinear diffusion equation (tFINDE) with Riemann–Liouville fractional derivative is studied. All point symmetries admitted by this equation are derived. The optimal system of one-dimensional subalgebras is classified to perform the symmetry reductions. It is shown that the tFINDE can be reduced to fractional ordinary differential equations (FODEs), including Erdélyi–Kober fractional derivatives. As the results, some explicit group-invariant solutions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Zhang [24] provided the symmetric determining equation and nonlinear method for solving fractional nonlinear partial differential equations. Feng [25][26][27] investigated the symmetry and conservation laws of various classes of time-fractional nonhomogeneous nonlinear diffusion equations. Chen [28] expanded the coefficients of fractional-order equation from constant coefficients to variable coefficients while conducting Lie symmetry analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [24] provided the symmetric determining equation and nonlinear method for solving fractional nonlinear partial differential equations. Feng [25][26][27] investigated the symmetry and conservation laws of various classes of time-fractional nonhomogeneous nonlinear diffusion equations. Chen [28] expanded the coefficients of fractional-order equation from constant coefficients to variable coefficients while conducting Lie symmetry analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Refs. [15][16][17][18][19][20][21][22][23] generalized this method to resolve fractional non-linear partial differential equations (fNPDEs). It is verified that by applying ISM, a fNPDE can be reduced to a system of fractional nonlinear ordinary differential equations (fNODEs), which can be solved by known analytical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gazizov et al established the modification of the invariant subspace method for FDEs [19], where they also found that the jointness of invariant subspace and the Lie symmetry group is helpful for finding exact solutions of FDEs. Based on these established schemas, numerous works have focused on FDEs, including scalar-time FDEs [20,21], multidimensional-time FDEs [22,23], coupled-time FDEs [24][25][26], and space-time FDEs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%